2008
DOI: 10.4148/2378-5977.7017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing glycerol and dried distillers grains with solubles on the growth performance and carcass characteristics of finishing pigs (2008)

Abstract: Effects of increasing glycerol and dried distillers grains with solubles on the Effects of increasing glycerol and dried distillers grains with solubles on the growth performance and carcass characteristics of finishing pigs growth performance and carcass characteristics of finishing pigs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
6
9
3
Order By: Relevance
“…There was no interaction between level of corn DDGS and crude glycerin fed. This agrees with work by Duttlinger et al (2012) who reported no interaction between corn DDGS fed at 0 or 200 g/kg and crude glycerin fed at 0, 25, or 50 g/kg. Similarly Lee et al (2013) reported that combining 300 g corn DDGS/kg diet with 50 g crude glycerin/kg diet did not impact ADG, ADFI, or G:F as compared to feeding diets containing either 300 or 0 g/kg corn DDGS.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There was no interaction between level of corn DDGS and crude glycerin fed. This agrees with work by Duttlinger et al (2012) who reported no interaction between corn DDGS fed at 0 or 200 g/kg and crude glycerin fed at 0, 25, or 50 g/kg. Similarly Lee et al (2013) reported that combining 300 g corn DDGS/kg diet with 50 g crude glycerin/kg diet did not impact ADG, ADFI, or G:F as compared to feeding diets containing either 300 or 0 g/kg corn DDGS.…”
Section: Resultssupporting
confidence: 93%
“…It has been shown that feeding increased amounts of corn DDGS to growing pigs increases the PUFA concentration particularly linoleic acid (C18:2), in pork adipose tissue (Benz et al, 2010,b;Xu et al, 2010a,b;Duttlinger et al, 2012), resulting in softer pork fat which decreases the overall quality of the pork carcass (NPB, 2000;Hilbrands et al, 2013). Feeding 100 g crude glycerin/kg diet to growing pigs has been shown to decrease linoleic acid (C18:2) content of pork adipose (Lammers et al, 2008a).…”
Section: Introductionmentioning
confidence: 97%
“…Similar results were found by other authors as Duttlinger et al (2008), Della Casa et al (2009), Hansen et al (2009) and Berenchtein et al (2010) who evaluated the meat texture with a Warner-Bratzler cell (WB). Although different methodology was used (WB vs. TPA), Caine et al (2003) found a positive correlation between the maximum force parameter obtained by the WB method and hardness (maximum force obtained during the first compression cycle) resulting from a TPA analysis.…”
Section: Texture (Textural Profile Analysis) Colour Coordinates (L*supporting
confidence: 79%
“…Hansen et al (2009) did not obtain an effect on BT-P2 of growing pigs (50.9 to 105.2 kg) fed with up to 16% semi purified mixed glycerin. Duttlinger et al (2008) did not find effect on the LD by including up to 5% of glycerin. The BT (Table 6) increased linearly (P≤0.05) with the inclusion of different levels of SPGM.…”
Section: Resultsmentioning
confidence: 66%